Effects of instruction and preparation on - Ahmari Tehran, H; Kachooei, A; Abedini, Z; Khorrami Rad, A (Advances in Nursing & Midwifery, 2009)
Background and aim Mammography is a method for screening cancer. Although its results usually show benign conditions, it is associated with known anxiety and depression in women during the procedure. This can affect on their desire to seek for checkups and assistance.This clinical trial was conducted to determine the effects of instruction and preparation on the anxiety of women referring to Izadi Mammography Center in Qom city. Materials and methods 160 women referring to the center for the first time were selected by convenience sampling method and randomly divided into 2 experimental and control groups. A demographic questionnaire and Beck’s anxiety inventory were used for data collection. Anxiety levels of the 2 groups were measured and compared before and after instruction and preparation phase. Different statistical tests were used for data analysis. Findings Mean anxiety scores of the experimental and control groups were 10.9±5.2 and 21.5±8.4 respectively with a significant difference (P<0.001). Anxiety level of the experimental group before mammography decreased than the beginning of the study (P<0.001) but it increased in the control group. Conclusion In general, consultation and preparation by different medical staff members can be effective in reducing anxiety levels of women during mammography. Keywords: Instruction, Preparation, Anxiety, Mammography. *Corresponding Author: Ahmari Tehran H; Lecturer, Faculty of Nursing and Midwifery, Qom University of Medical Sciences. E-mail: ahmari9929@yahoo.com